Who Doesn't Want to be an Entrepreneur? The Role of Need for Closure in Forming Entrepreneurial Intentions of Polish Students - Aleksandra Wąsowska (Entrepreneurial Business and Economics Review, 2016)
Objective: The objective of this paper is to broaden our understanding of the factors that shape entrepreneurial intention (EI). Specifically, we analyse how the need for cognitive closure (NfC) influences EI.